Monitoring the Future: A Continuing Study of American Youth (12th-Grade Survey), 2022 - Miech, Richard A. ([Verlag nicht ermittelbar], 2023)
This survey of 12th-grade students is part of a series that explores changes in important values, behaviors, and lifestyle orientations of contemporary American youth. Students are randomly assigned to complete one of six questionnaires, each with a different subset of topical questions, but all containing a set of "core" questions on demographics and drug use. There are about 1,400 variables across the questionnaires. Drugs covered by this survey include tobacco, smokeless tobacco, alcohol, marijuana, hashish, prescription medications, over-the-counter medications, LSD, hallucinogens, amphetamines (stimulants), Ritalin (methylphenidate), Quaaludes (methaqualone), barbiturates (tranquilizers), cocaine, crack cocaine, GHB (gamma hydroxy butyrate), ecstasy, methamphetamine, and heroin. Other topics include attitudes toward religion, changing roles for women, educational aspirations, self-esteem, exposure to drug education, and violence and crime (both in and out of school). Highlights for 2022: Continuation of randomized blocks of questions presented to students. Please see Appendix D of the codebook. Change to the question stem for some lifetime, 12 month, and 30 day heroin and marijuana use questions. Please see the Highlights for 2022 section in the codebook for more details. Change to the heroin use questions: Separate questions about heroin use with a needle and heroin use without a needle for lifetime, past 12 months, and past 30 day timeframes are no longer asked. The separate questions have been replaced by the single question, "On how many occasions (if any), have you taken heroin... ...in your lifetime? ...during the last 12 months? ...during the last 30 days? Please see the Highlights for 2022 section in the codebook for more details. Additional information is documented in the MTFQchanges2022byForm.pdf and MTFQchanges2022byType.pdf files available for download.